Demokrasi yang Tergerus Oleh Dominasi Negara Atas Rakyat dalam Politik - Rasji; Destiana Vani Candra; Devika Graciella Gunawan; Kaniko Dyon Geraldi (Jurnal Hukum Lex Generalis, 2024)
According to Article 1(3) of the 1945 Constitution of the Republic of Indonesia, Indonesia is a rule of law state, meaning that governance must be conducted based on legal principles. The concept of a rule of law state is closely related to the democratic system implemented in Indonesia. Democracy is a system of government that emphasizes the principle of popular sovereignty, in which the people hold the highest power in state governance. However, despite the people's fundamental role in shaping and directing the country, Indonesia's democracy index has shown a decline. This study aims to analyze the causes of democratic decline in Indonesia and the consequences of democratic erosion. The research adopts a normative legal approach, utilizing secondary data from journals, articles, and legislation. The findings reveal that, in practice, democracy often experiences distortions. As a result, Indonesia's democracy has significantly deteriorated, dropping three places in 2024 to rank 59. To address this issue, several solutions can be implemented. First, the government must ensure freedom of speech, expression, and the press to uphold democratic values. Second, public access to government information must be improved to promote transparency and accountability. Third, it is essential to strengthen the performance of government institutions, including the legislative, executive, and judicial branches, to prevent the concentration of power in a single entity. Lastly, enhancing the legal framework is necessary to impose stricter deterrents against violations of democratic principles. Thus, to prevent further democratic decline and safeguard Indonesia's democratic integrity, the government must evaluate its governance practices and ensure that democracy remains a true reflection of the people's sovereignty rather than a system dominated by the state.